IMPLEMENTATION OF THE MERDEKA CURUUCULUM IN MADRASAH IBTIDAIYAH IMPACT ON LEARING QUALITY - Lesmana, Nadella; Hasnanto, Anton Tri (Jurnal Ecoment Global, 2024)
Objective: This study aims to analyze the implementation of the Merdeka Curriculum in Madrasah Ibtidaiyah and its impact on the quality of learning. The Merdeka Curriculum is designed to provide freedom in the teaching and learning process, with an emphasis on the development of student competencies and character, and is expected to improve the quality of education at various levels, including madrasahs. Design/Methods/Approach: Using a research method that involves a literature review discussing the implementation of the Merdeka Curriculum and the issues faced in Madrasah Ibtidaiyah related to the impact on the quality of learning in the field. Findings: The research findings indicate that the implementation of the Merdeka Curriculum in Madrasah Ibtidaiyah has a positive impact on the quality of learning, particularly in enhancing student participation, the development of critical thinking skills, and collaborative abilities. Originality/Value: this research also identifies several challenges, such as limited resources and the need for intensive training for teachers to effectively implement the curriculum Practical/Policy implication: In conclusion, although the implementation of the Merdeka Curriculum shows potential to improve the quality of learning, the success of its implementation heavily depends on adequate infrastructure support and the readiness of educators.